Mutu Pelayanan Puskesmas dengan Status Akreditasi di Puskesmas - Duha, Sonya Marsela Pieta; Ginting, Chrismis Novalinda; Nasution, Ali Napiah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aimed to see the relationship between service quality and the accreditation status of the Health Center. The research method used a cross-sectional study. Data were collected using a questionnaire sheet. The collected data were analyzed using the Chi-Square test. The study's results showed a significant relationship between the service quality dimensions (responsiveness, assurance, tangible, empathy, and reliability) and the accreditation status of the health center. This study concludes a relationship between responsiveness, assurance, tangible, empathy, and reliability with accreditation status. Keywords: Accreditation, Service Quality, Health Center